A new species of the genus Scutiger (Anura: Megophryidae) from southeastern Tibet, China - Jiang, Ke; Rao, Dingqi; Yuan, Siqi; Wang, Jishan; Li, Pipeng; Hou, Mian; Che, Maihe; Che, Jing (Zootaxa, 2012)
A new species of Scutiger Theobald, 1868 is described from Medog, southeastern Tibet, China. Scutiger wuguanfui sp.nov. is distinguished from congeners in the following combination of characters: (1) large adult size, female is much largerthan male; (2) maxillary teeth absent; (3) male with a pair of pectoral glands and a pair of axillary glands, axillary glandssimilar to pectoral glands, all of them covered by black spines in breeding season; (4) in breeding male, nuptial spines ondorsal surface of firs and second fingers, and inner side of third finger; (5) male with an internal single subgular vocal sac,a pair of slit-like openings of vocal sac near corners of the mouth. This new species is currently known only from the type locality.